Women's contributions to radiobiology in Ireland; from small beginnings…. (4th March 2022) - Howe, Orla; Lyng, Fiona M.; Mothersill, Carmel
Abstract: Objectives: To describe the contribution of women radiobiologists in Ireland to the development of the discipline internationally and at home and to discuss the history of radiobiology in Ireland to date. This parallels the history of the evolution of a small radiobiology group in Kevin Street, Dublin Institute of Technology (DIT) which was formerly part of the City of Dublin Vocational Education Committee. There followed years of development first as a radiobiological research center which evolved in the FOCAS Research Institute now embedded within Technological University Dublin (TU Dublin). Conclusions: Over the last 45 years, the women of the Radiation and Environmental Science Centre (RESC) contributed to the major paradigm shift in low dose radiobiology contributing exciting new research concerning non-targeted effects, including discovery of lethal mutations, medium transfer bystander mechanisms, and signaling pathways. They also developed translational research using human explant culture systems with unique immunocytochemical methods and more recently evolved to molecular and spectroscopic analysis of clinical samples. The RESC also developed unique in vitro research methods into effects of radiation on non-human species of concern in ecosystems.